The Relating to Knowdwdge Pregnant Women to Danger Signs Pregnancy - Musmundiroh, Musmundiroh (Jurnal MIDPRO, 2023)
Pregnancy that is the first time experienced by a newly pregnant mother or what is called (Primigravida) is a special experience for every pregnant mother, prospective mothers who are newly pregnant do not have experience regarding matters related to pregnancy, especially danger signs during pregnancy, in mothers whose age is 20 year olds experience a higher risk of birth problems and perinatal complications compared to mothers who have given birth.The results of the bivariate study showed that there was no employment relationship (p=0.142), while the related bivariates were age (p=0.047), education (p=0.008), parity (p=0.009) and sources of information (0.014). The results of the multivariate test showed that education (p=0.032) and parity (p=0.033) had the most significant relationship with mother's knowledge of pregnancy danger signs. Based on the results of this study, it is recommended to provide outreach to pregnant women who are in the research environment to be able to understand pregnant women's knowledge of danger signs of pregnancy so that pregnant women care even more about their pregnancy.